Quality Evaluation of Deep Frozen Scraped Coconut - Samarakone, H. S. M. D. S. M.; Yalegama, Loku Liyana Waduge Chandi (International Coconut Community, 2014)
Fresh scraped coconut is highly susceptible to rancidity and microbial spoilage. Consumer acceptability of frozen scraped coconut in terms of chemical, microbiological and sensorial quality for three months of storage period was aimed in this study. Scraped coconut was taken and steam blanched for 5, 10 and 15 minutes using steamer. Half of blanched coconut was mixed with Vitamin E at 500 ppm. Then it was packed in LLDPE/PET/Al pouches (200 g/pouch) and sealed and stored under frozen condition at -18°C using a domestic freezer for 3 months. Control treatment was carried out by keeping the untreated grated coconut at frozen condition. Total plate count (TPC), free fatty acid (FFA) and peroxide values (PV) were measured in two week intervals for 3 months. Sensory properties of frozen coconut samples were tested in monthly intervals. Results revealed that significantly low FFA values in all the treated samples compared to control. The concentrations were below the detectable levels of rancidity (1% as lauric acid). There was no peroxide value detected throughout the study period in both the control and treated samples. It was evident that an inverse relationship occurred between TPC values and blanching time. No differences were seen in sensory attributes in all frozen coconut and were within acceptable range. Application of steam blanching for 15 minutes with/without addition of vitamin E on fresh scraped coconut has the best advantages to extend the shelf life for minimum of three months to preserve the organoleptic properties at domestic frozen conditions.